Sistem E-Learning Pada SMA Dharma Bakti 3 Kota Jambi - Mubarak, Ahmad Zaky; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2021)
SMA Dharma Bakti 3 Kota Jambi is one of school which has been located in Jambi where the process of teaching done in schools and the spread of information using the bulletin board. So always get problem like The limited time and place in teaching, students hard to get matter learning complete, discussions that can happen only in schools and distribution of information limited at school. Because of that, this research have purpose to give solution to that happening problems with offer a e-learning application by using PHP programming language and MySQL database with prototype and using model approach system unified model language with use case diagram, activity diagram, class diagram and flowchart diagram. So application can be used by admin, teachers, students who made in obtaining learning matter, timetables, doing the exercise online and get the latest information website made.